Indonesia The Position Of Muslim Women From The Perspective Of The Quran: A Critique Of Feminism - Lahmuddin, Lahmuddin; Oki, Alber; Sinaga, Henri Toga (ZAD Al-Mufassirin, 2024)
The purpose of this study is to analyze the position of Muslim women from the perspective of the Qur'an: Refuting feminism. This research uses a qualitative approach and is a literature study. Based on the results of the study, feminism and its movement demanding gender equality are hotly discussed among academics in education, media and government. Gender is defined as a trait attached to men and women that is socially and culturally constructed, for example, women are known as gentle, emotional, or motherly, while men are considered strong, rational, male and mighty. Over time, this notion entered Islam and indoctrinated its thinkers. Various sharia in Islam that are considered demeaning to women are discussed, their laws are criticized, considered discriminatory, subordinate and detrimental to women. According to feminism, sharia rules make the position of women degraded and not treated fairly.  However, in fact, in Islamic teachings the role of women is very important and women are even one of the pillars that support the strength of a family, community, and even nation and state. The Quran and tafsir glorify women and explain their position as equal to men, only taqwa to Him distinguishes the two.